SITUATIONAL CONTROL OF HOT BLAST STOVES GROUP BASED ON DECISION TREE - E. I. Kobysh (Avtomatizaciâ Tehnologičeskih i Biznes-Processov, 2016)
In this paper was developed the control system of group of hot blast stoves, which operates on the basis of the packing heating control subsystem and subsystem of forecasting of modes duration in the hot blast stoves APCS of iron smelting in a blast furnace. With the use of multi-criteria optimization methods, implemented the adjustment of control system conduct, which takes into account the current production situation that has arisen in the course of the heating packing of each hot blast stove group. Developed a situation recognition algorithm and the choice of scenarios of control based on a decision tree.